Extraction, phytochemical characterization, and antifungal activity of Salvia rosmarinus extract - Aamer Helmy A.; Al-Askar Abdulaziz A.; Gaber Mahmoud A.; El-Tanbouly Rania; Abdelkhalek Ahmed; Behiry Said; Elsharkawy Mohsen M.; Kowalczewski Przemysław Łukasz; El-Messeiry Sarah (Open Chemistry, 2023)
In the current study, we used high-performance liquid chromatography (HPLC) and gas chromatography–mass spectrometry (GC–MS) to investigate and analyze the methanolic extract of Salvia rosmarinus leaves. HPLC analysis showed that the extract revealed a diverse array of polyphenolic compounds, including apigenin, catechin, chlorogenic acid, cinnamic acid, caffeic acid, coumaric acid, daidzein, ellagic acid, ferulic acid, gallic acid, hesperetin, kaempferol, methyl gallate, naringenin, pyrocatechol, quercetin, rutin, syringic acid, and vanillin. Furthermore, three fungal isolates from symptomatic strawberry plants were obtained and identified as Botrytis cinerea (OR116486), Fusarium oxysporum (OR116505), and Rhizoctonia solani (OR116525). The extract’s antifungal activity was evaluated at concentrations of 0, 50, 150, 200, and 300 µg/mL. At 200 µg/mL, the extract showed growth inhibition percentages of 74.56, 58.19, and 56.67% for R. solani, F. oxysporum, and B. cinerea, respectively, while at 300 µg/mL, all the tested fungi were completely suppressed. The GC–MS analysis revealed that the major compounds of the methanolic extract identified based on their retention times and relative peak areas (%) included β-caryophyllene (12.06%), germacrene d (13.55%), caryophyllene oxide (3.13%), methyl palmitate (5.26%), hexadecanoic acid (4.9%), and methyl stearate (6.02%). These results show rosemary extract’s potential as a source of natural antifungal agents against plant photogenic fungi. As a result, it provides a safer alternative to the current protective approaches for plant disease management.